Federalism: “New Malaysia” and hope for the state of Kelantan / Wan Zulfadhli Syahman Wan Yusof, Tuan Nooriani Tuan Ismail and Iskandar Hasan Tan Abdullah - Wan Yusof, Wan Zulfadhli Syahman; Tuan Ismail, Tuan Nooriani; Tan Abdullah, Iskandar Hasan (Universiti Teknologi MARA, 2022)
Malaysia consists of 13 states and three Federal Territories, practicing the concept of federalism in its governing system. The Federal Government of Malaysia was governed by only a single-party coalition known as Perikatan, later renamed Barisan Nasional (BN) in 1973. However, in the 14th General Election, which was held in May 2018, for the first time, the country’s administration was replaced by another political coalition known as Pakatan Harapan (PH). The main objective of this article is to emphasize the future of the relationship between the Kelantan State Government and the Federal Government of Malaysia, especially post the 14th general election. The selection of Kelantan as the focus of this article is important because, in the context of Malaysian democracy, the state is the longest-running state under a different party administration from the Federal Government, which directly offers a certain perspective on the relationship between the Federal and State Governments. This article specifically referred to related documents covering articles, journals, writings, speeches, and references to any form of communication and observation of the commitments that have been made by the Kelantan State Government and the Federal Government of Malaysia.